PENEBANGAN LIAR (ILLEGAL LOGGING) DI VANUATU BERDASARKAN UNITED NATIONS FRAMEWORK CONVENTION ON CLIMATE CHANGE: Illegal Logging In Vanuatu Based On The United Nations Framework Convention On Climate Change - Imam makkarim mukhtar lubis; Sugeng Supartono (Faculty of Law, Universitas Trisakti, 2025)
Climate change is a global challenge that impacts small island states, including Vanuatu. This study examines policies based on the United Nations Framework Convention on Climate Change in Vanuatu's climate change mitigation efforts, on reducing carbon emissions and increasing environmental resilience. Identify of this stufy; violations committed by Vanuatu against the provisions of the United Nations Framework Convention on Climate Change (UNFCCC) and Vanuatu's responsibilities in addressing illegal logging violations under the UNFCCC. Normative and descriptive legal research methods, this study highlights Vanuatu's role in fighting for climate justice, despite challenges such as weak law enforcement, dependence on foreign aid, and limited implementation capacity. The results and the conclusion of the study indicate that although Vanuatu has taken strategic steps in reducing carbon emissions through international cooperation and local policies, there are still obstacles to implementation. This study recommends increasing the contribution of developed countries in supporting developing countries and strengthening local institutions to ensure the sustainability of mitigation policies. These findings provide important insights for global efforts to address climate change through more effective collaboration between developed and developing countries.